2023
DOI: 10.1080/10985549.2023.2284147
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Pharmacological Modulation of Cellular Proteostasis Leads to Partial Functional Rescue of Homocystinuria-Causing Cystathionine-Beta Synthase Variants

Renata Collard,
Tomas Majtan

Abstract: Homocystinuria (HCU), an inherited metabolic disorder caused by lack of cystathionine beta-synthase (CBS) activity, is chiefly caused by misfolding of single amino acid residue missense pathogenic variants. Previous studies showed that chemical, pharmacological chaperones or proteasome inhibitors could rescue function of multiple pathogenic CBS variants; however, the underlying mechanisms remain poorly understood. Using Chinese hamster DON fibroblasts devoid of CBS and stably overexpressing human WT or mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Utilization of these two alternative pathways to dispose of pathogenic CBS variants may potentially be related to the induction of ER stress due to CBS misfolding and aggregation (or formation of higher‐molecular weight complexes). Previously we showed that the expression of CBS I278T variant significantly upregulates expression of several cytoplasmic molecular chaperones and substantially increases the expression of BiP, an ER sensor of unfolded protein response (Collard & Majtan, 2023 ; Cyr & Hebert, 2009 ) indicating involvement of ER in proteostasis of HCU CBS variants. ALP is the second main pathway for protein degradation after UPS, typically used for protein aggregates and organelles (Siva Sankar & Dengjel, 2020 ).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Utilization of these two alternative pathways to dispose of pathogenic CBS variants may potentially be related to the induction of ER stress due to CBS misfolding and aggregation (or formation of higher‐molecular weight complexes). Previously we showed that the expression of CBS I278T variant significantly upregulates expression of several cytoplasmic molecular chaperones and substantially increases the expression of BiP, an ER sensor of unfolded protein response (Collard & Majtan, 2023 ; Cyr & Hebert, 2009 ) indicating involvement of ER in proteostasis of HCU CBS variants. ALP is the second main pathway for protein degradation after UPS, typically used for protein aggregates and organelles (Siva Sankar & Dengjel, 2020 ).…”
Section: Discussionmentioning
confidence: 96%
“…In this study, we established a new cellular model of HCU based on human HEK293 cells and utilized it to study proteostasis of CBS in health and disease. In the past, we and others have used cellular models heterologously expressing human CBS variants in bacterial cells (Kozich et al, 2010 ; Majtan et al, 2010 ), yeast (Kruger et al, 2003 ; Kruger & Cox, 1994 ; Majtan et al, 2008 ), mammalian Chinese hamster cells (Collard & Majtan, 2023 ; Maclean et al, 2002 ) in addition to skin fibroblasts derived from HCU patients (Janosik et al, 2001 ; Lipson et al, 1980 ; Maclean et al, 2002 ; Skovby et al, 1982 ). The bacterial models were useful for high‐yield production of CBS variants for detailed biochemical and biophysical characterizations, but they are unsuitable for clarification of molecular mechanisms responsible for CBS proteostasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations